Enhancing enzyme digestibility of red tilapia (Oreochromis niloticus and O. mossambicus) and improving water quality in fish farming using Napier grass silage - Kuangkam, Pimwaranee; Whangchai, Niwooti; Pimpimol, Tipsukhon; Senphan, Theeraphol; Puntharod, Rutchadaporn; Sompong, Udomluk (Agriculture and Natural Resources, 2024)
Importance of the work: Utilizing locally available and more affordable plant-based raw materials could mitigate the increasing costs of raw fish feed ingredients. This study should enhance understanding regarding using Napier grass (Pennisetum purpureum ‘Pak Chong 1’) as a fish feed ingredient and its effect on fish, digestive enzyme activities and water quality in aquaculture. Objectives: To assess the efficacy of different processed forms of Napier grass as a feed ingredient for red tilapia (hybrid between Oreochromis niloticus and O. mossambicus) and efficacy of extracted tannins in reducing the ammonia content in water. Materials & Methods: The in vitro digestibility was analyzed of four Napier grass variants (dried, fresh, fermented and boiled). Proteolytic, amylase and cellulase enzyme activity levels were assessed.Tannin extraction was used to evaluate the efficiency of Napier grass extracts in reducing water ammonia levels based on the microwave method, which yielded a higher tannin content than the reflux method. Then, the extracted tannins were applied to water samples to examine their efficacy in reducing the ammonia content. Results: The red tilapia fed fermented Napier grass (SN) had the highest enzymatic activity, with trypsin activity at 0.439 µmol DL-lanine/g feed, amylase activity at 0.828 µmol maltose/g feed, while the cellulase activity was 587.123 µmol maltose/g feed (p < 0.05). The application of Napier grass extracts successfully reduced the ammonia content in the water samples at 0.15 mg/l NH3-N/g dry Napier grass. Evidence for the binding of tannic acid and ammonium ion was identified. Main finding: Napier grass, particularly in its fermented form, can serve as an effective alternative feed for aquaculture. Tannin extracted from Napier grass efficiently reduced the ammonia content in water.